Participation in a Currency Union - Casella, Alessandra (American Economic Review, 1990)
In any voluntary cooperative agreement, the potential gain from deviation should determine the minimum influence required over common decision-making. This paper begins by observing that a highly asymmetric distribution of power between two partners is not sustainable if the choice variables are strategic substitutes. It then studies a simple general-equilibrium model of a monetary union and shows that a small economy will not take part in the agreement unless it can secure influence that is more than proportional to its size and a transfer of seigniorage revenues in its favor. Copyright 1992 by American Economic Association.